Constructive feedback as a learning tool to enhance students’ self-regulation and performance in higher education - Erna du Toit (Perspectives in Education, 2012)
If feedback is provided in a way that can develop students’ self-regulatory skills, it could enhance learning and, consequently, lead to improved performance. To improve teaching and learning in higher education (HE), this study sought to determine whether the feedback to first-year students affords them an opportunity to learn from it. A theoretical framework on constructive feedback, self-regulated learning and the expectations of students was synthesised from literature which formed the basis of the research. This was followed by empirical research using a questionnaire to capture students’ perspectives regarding feedback. Students experienced the feedback as not contributing towards improving their performance but are convinced that, if they receive feedback that is focused on the task level, it can improve their performance. Suggestions are provided that emphasise the need to use feedback at both task and process level as a learning tool.